Design Of a Strategic Planning for The Company MetalProffice S.A.S in Cartagena-Colombia (2021)
The following research work proposes the creation and implementation of a strategic planning for the company Metal Proffice S.A.S. For which a methodology was used that allowed to collect integral information of the company, with the help of tools it was possible to obtain an internal and external diagnosis of the company and thus be able to identify the shortcomings where it should be reinforced. In addition, it was possible to propose the objectives and strategic plans that would commit all the company's stakeholders to consolidate those activities that would provide a better competitive position and a significant improvement in the production areas. Finally, certain recommendations are given for the owners of the company so that they can have a long-term vision of the benefits of the project.